Materialism and Religious Perspective: An Analysis of Karl Marx's Thought - Juwaini, Juwaini; Yasin, Taslim HM; Safira, Cut Siska (Abrahamic Religions: Jurnal Studi Agama-Agama, 2024)
Karl Marx was a philosopher and social observer, whose intelligence and brilliant thinking earned him a position as a political leader among the proletarian class of his time. For Marx, the essence of humanity lies in labor, and religion is a product and expression of the interests of the oppressed lower classes. Living in Europe during the industrial age, Marx's thoughts differed significantly from those of other philosophers of his time. This text examines Marx's thoughts on Materialism, religious beliefs, and Marxist Economics. Research findings indicate that Historical Materialism proposed by Marx is a useful term for providing the basic assumptions of his theory. The emphasis in his work "Das Kapital" is on the material needs and the struggle to enhance socialist revolution so that the proletariat can enjoy the majority of what is produced by industrialism. Marx believed that the ownership of the means of production in society should be evenly distributed according to human needs, not to the greed of a few. Religion, Marx argued, is an opiate for the masses, manipulating them with promises of eternal futures, thus alienating them from reality. In the capitalist economic system, Marx contended that fair wages for labor should be determined equally, just as the value of each commodity is determined by the amount of labor, meaning that employers should pay workers according to their labor